2021
DOI: 10.1101/2021.01.15.21249691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 viral load distribution reveals that viral loads increase with age: a retrospective cross-sectional cohort study

Abstract: ObjectiveTo describe the SARS-CoV-2 viral load distribution in different patient groups and age categories.MethodsAll SARS-CoV-2 RT-PCR results from nasopharyngeal (NP) and oropharyngeal (OP) swabs (first PCR from unique patients only) that were collected between January 1 and December 1, 2020, predominantly in the Public Health Services regions Kennemerland and Hollands Noorden, province of North Holland, the Netherlands were included in this study. Swabs were derived from patients with respiratory symptoms w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
6
27
1
1
Order By: Relevance
“…The high heterogeneity observed was influenced by age and gender, as evidenced by the meta-regression. These findings are in accordance with some previous analyses demonstrating that the viral load increases with age [ 21 ] and is higher in females [ 22 ]. However, we also cannot use underlying comorbidities, such as arterial hypertension and diabetes, as moderator variables, which have been related to a slower viral shedding [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…The high heterogeneity observed was influenced by age and gender, as evidenced by the meta-regression. These findings are in accordance with some previous analyses demonstrating that the viral load increases with age [ 21 ] and is higher in females [ 22 ]. However, we also cannot use underlying comorbidities, such as arterial hypertension and diabetes, as moderator variables, which have been related to a slower viral shedding [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings somehow differ from adult data, where sensitivity remained high throughout the first five DPOS (despite being lower at 0 DPOS) ( 6 ), likely here again reflecting the impact of higher VLs in adults on P-RDT sensitivity. Similarly, the trend toward lower sensitivity in children <12 years old is likely explained by lower VLs in younger children, as seen in this study and other publications ( 17 19 ). Among symptomatic participants, sensitivity was better in those with COVID-19-typical symptoms, as previously shown in adults ( 6 ), but also in those with >2 symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, although initial studies suggested similar VLs in adults and children, they were limited in sample size and did not take into account DPOS ( 13 15 ), which is a major determinant of VL ( 16 ). Recently, studies on larger data sets and/or taking into account DPOS have shown that SARS-CoV-2-infected children have significantly lower VLs than adults ( 17 19 ). Another possible explanation for the lower sensitivity could be sampling bias related to the technical challenge of the NPS procedure in children, given that the swab for the P-RDT testing was the second one to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include patient age, duration of illness, and antibody sero-status at the point of presentation. [13][14][15] We hypothesised that the association between viral load and clinical outcome seen in early studies may be dependant on other factors rather than independently associated. The aim of the study was therefore to evaluate the association between viral load, as measured by real-time PCR cycle threshold (Ct) value, and outcome whilst carefully adjusting for covariates including age, duration of illness and antibody sero-status.…”
Section: Introductionmentioning
confidence: 99%